2005
DOI: 10.1007/s10439-005-7257-7
|View full text |Cite
|
Sign up to set email alerts
|

On the Passive Cardiac Conductivity

Abstract: In order to relate the structure of cardiac tissue to its passive electrical conductivity, we created a geometrical model of cardiac tissue on a cellular scale that encompassed myocytes, capillaries, and the interstitial space that surrounds them. A special mesh generator was developed for this model to create realistically shaped myocytes and interstitial space with a controlled degree of variation included in each model. In order to derive the effective conductivities, we used a finite element model to compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 32 publications
10
95
0
Order By: Relevance
“…On the other hand, detailed spatial models have shown that geometry plays an important role in the conduction velocity but are too expensive to implement for a full 3D tissue (11,12,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…On the other hand, detailed spatial models have shown that geometry plays an important role in the conduction velocity but are too expensive to implement for a full 3D tissue (11,12,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…In previous work, simulations aimed at computing the bulk conductivity of tissue using the same underlying tissue model showed that reducing the extracellular space raised the impedance both along as well as across the fiber [6]. Hence, the examples presented in this paper show that one cannot directly translate the changes in macroscopic tissue conductivity into the bidomain model, as the bidomain model predicts assumes a similar relation between resistance and propagation velocity for both directions.…”
Section: Discussionmentioning
confidence: 82%
“…The geometrical model that underlies the simulation was based on previous work that focused on computing passive electrical characteristics of myocardial tissue such as the conductivity tensor for a bidomain [2,6]. We created a computer algorithm for filling up a space with realistically shaped myocytes that fit together like pieces of a jigsaw puzzle of which the average length and cross section could be altered to fit histological data.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular resistivity is higher in transverse than in longitudinal direction. Thus, anisotropy in the intracellular space ranges from ∼5 to 10 (Clerc, 1976;Roberts and Scher, 1982;Stinstra et al, 2005) and mainly results from cardiomyocyte shape and cellular distribution of connexins. In many cardiac diseases the expression of connexins (Cx43, Cx40, Cx45) is altered.…”
Section: Anisotropy and Non-uniformity (Inhomogeneity)mentioning
confidence: 99%
“…The concept of electrical anisotropy also applies to resistivity of the extracellular space and, besides influencing impulse propagation, has a strong effect on the distribution of epicardial potentials (Roberts and Scher, 1982;Johnston et al, 2001;Stinstra et al, 2005;Schwab et al, 2013). Experimental and computational studies reported anisotropies in the extracellular space ranging from 1.5 to 3.5 (Clerc, 1976;Roberts et al, 1979;Stinstra et al, 2005;Hand et al, 2009).…”
Section: Anisotropy and Non-uniformity (Inhomogeneity)mentioning
confidence: 99%